Quality of Life in Wilson’s Disease: A Systematic Literature Review - Chakrapani Balijepalli; Kevin Yan; Lakshmi Gullapalli; Stephane Barakat; Helene Chevrou-Severac; Eric Druyts (Journal of Health Economics and Outcomes Research)
**Background:** Wilson’s disease (WD) is a rare inherited genetic disorder characterized by the progressive accumulation of copper in the brain, liver, and other major organ systems. To date, there have been no comprehensive studies synthesizing evidence pertaining to the quality of life (QOL) in WD. **Objective:** We conducted a systematic literature review to identify and synthesize the evidence on QOL in patients with WD. **Methods:** To address this gap in the literature, we conducted a systematic literature review in MEDLINE and EMBASE to identify observational studies and clinical trials reporting QOL outcomes among people living with WD. **Results:** A total of 442 publications were identified, 41 publications were eligible for full-text screening, and 7 articles, representing 7 studies, met all inclusion criteria. QOL questionnaires used across studies included the 12-Item Short Form Health Survey Questionnaire (version 1) (SF-12) (n=2), the 36-Item Short Form Health Survey Questionnaire (version 1) (SF-36) (n=3), Global Assessment Scale (GAS) (n=1), and World Health Organization QOL brief questionnaire (WHO-QOL-BREF) (n=1). Overall, the pattern in QOL from most studies demonstrated a worse QOL in WD patients compared with the general population, a deterioration in QOL for patients presenting with neurologic symptoms, and more frequent psychiatric symptoms compared with the ones with hepatic symptoms. **Discussion:** Although our understanding of the underlying pathophysiology of WD has advanced, and novel therapeutics are on the horizon, our understanding of how WD affects overall QOL remains limited. Evidence from this review demonstrates the substantial heterogeneity in reporting outcomes pertaining to the QOL associated with WD. These differences may be attributable to the fact that QOL is not typically assessed and the lack of a standardized method for assessing QOL in WD. **Conclusion:** This review demonstrates a need for more up-to-date studies with larger sample sizes to further evaluate QOL in patients with WD. The study also demonstrates the need for a WD-specific instrument to measure the QOL in WD patients.